MALE-BIASED MOVEMENT IN A HIGH-DENSITY POPULATION OF THE EURASIAN BADGER (MELES MELES) - Macdonald, D; Newman, C; Buesching, C; Johnson, P (2008)
We investigated movement patterns in a high-density population of Eurasian badgers (Meles meles) to explore how the costs and benefits of dispersal and other forms of movement differed among individuals in the population. We analyzed a 17-year data set comprising 5,255 trapping events for members of a population of Eurasian badgers at Wytham Woods, Oxford, United Kingdom. For a subset of badgers with a sufficient trapping history, we were able to identify dispersal events. Permanent dispersal was not common. Of 267 badgers 1st trapped as young and caught on a minimum of 4 occasions spanning 400 days or more, the majority (75.8%) were never captured at more than 2 social groups. Only 51 (19.1%) of these animals satisfied our definition of dispersal; 96 (35.8%) were never captured outside of their natal social group. Male badgers moved between groups more than did females and accumulated more wounds in the process. Dispersing males tended to move to larger groups and to groups with a preponderance of females, but dispersal rate did not change as the density of the population increased. However, evidence of extraterritorial matings suggests that inbreeding may be alleviated without dispersal. We consider the implications of these findings for the mating system and social behavior of the badger. © 2008 American Society of Mammalogists.